Design and Built an Expert System Application Fir Diagnosing Human Eye Diseases by using Forward Cahining Metodh Web-Based - Harkamsyah Andrianof (Universitas Putra Indonesia YPTK Padang, 2021)
The eye is one of the five senses that has a very important role in human life, namely as the organ of vision. If there is interference with the eye or there is a disease, it is very influential on human vision. Its mean that we can conclude that eye is very important in our lie and must be keep for our body. The purpose of this research to planning and develop the diagnose of expert system about diagnosing of diseases in the eye which include disease information about symptoms or the solution and have role to replace and imitate the process of the reason from an expert in solve the specification problem. the method used for reasoning is forward chaining method. The result of this research is expert system of diagnosing eyes diseases in humans which computerized who can be used for giving information and have benefit in diagnosing disease